Characteristics of socially successful elementary school‐aged children with autism. (13th September 2016) - Locke, Jill; Williams, Justin; Shih, Wendy; Kasari, Connie
Abstract : Background: The extant literature demonstrates that children with autism spectrum disorder (ASD) often have difficulty interacting and socially connecting with typically developing classmates. However, some children with ASD have social outcomes that are consistent with their typically developing counterparts. Little is known about this subgroup of children with ASD. This study examined the stable (unlikely to change) and malleable (changeable) characteristics of socially successful children with ASD. Methods: This study used baseline data from three intervention studies performed in public schools in the Southwestern United States. A total of 148 elementary‐aged children with ASD in 130 classrooms in 47 public schools participated. Measures of playground peer engagement and social network salience (inclusion in informal peer groups) were obtained. Results: The results demonstrated that a number of malleable factors significantly predicted playground peer engagement (class size, autism symptom severity, peer connections) and social network salience (autism symptom severity, peer connections, received friendships). In addition, age was the only stable factor that significantly predicted social network salience. Interestingly, two malleable (i.e., peer connections and received friendships) and no stable factors (i.e., age, IQ, sex) predicted overall social success (e.g., high playground peer engagement and social network salience) in children with ASD. Conclusions: School‐based interventions should address malleable factors such as the number of peer connections and received friendships that predict the best social outcomes for children with ASD.